Isolation and diagnosis of some fungi associated with surface and digestive of Periplaneta americana L.(Orthoptera: Blattidae) in Karbala governance and Potential Biological Control of them - Baqir, Hussein Ali (Journal of Kerbala for Agricultural Sciences, 2018)
This study was conducted in Karbala governance‏ during 2014, for isolation and identification of some fungi from surface and digestive of Periplaneta americana L.(Orthoptera: Blattidae). The insect samples were collected from women's and obstetricians hospital and residential areas near of the hospital. The study showed isolation and identification several fungi that were Aspergillus niger, A.fumigatus , Trichoderma harzianum , Penicillium sp. , Alternaria sp. , Mucor sp. and Fusarium sp from surface and digestive of P. americana. The Aspergillus niger was the highest percentage frequency about 26.32%, compared with other fungi while the lowest percentage frequency was recorded for Mucor sp. with 1.75%. The pathogenicity test indicated to the potential effect of Trichoderma harzianum against adult of P. Americana. The T. harzianum suspensions were applied on the adult either by direct spraying or as bait. The bait method reached mortality 80% of the insect with fungal concentration 17x 107 after 10 day compared with direct spraying that was reached 40% mortality with same fungi in concentration above after same period.